Opportunities and challenges organo-mineral fertiliser can play in enabling food security - Sakrabani, Ruben (Frontiers in Sustainable Food Systems, 2024)
Food security is a growing challenge related to an increasing global population. The agricultural sector is key for a secure supply of food but relies up to 50% on mineral fertilisers to meet crop nutrient demands. As mineral fertilisers production is energy intensive, causing close to 2% of global greenhouse gas (GHG) emissions, this poses greater challenge to meet net zero targets. Other challenges include extreme weather patterns, GHG during fertiliser applications and diffuse pollution, declining soil health, pest, disease, and loss of soil biodiversity. As mineral fertilisers’ price increases and the state of soil health decreases, innovative solutions are needed to meet crop nutrient demands while ensuring that sufficient organic matter is conserved in the soil. One solution to achieve net zero in agriculture can be in the form of organo-mineral fertilisers (OMF). OMFs are a new concept that take organic feedstock (such as biosolids, livestock manure, crop residues, food waste) and combines them with reduced amounts of mineral fertilisers resulting in a balanced fertiliser product. This Perspective piece discusses a Strength-Weakness-Opportunities-Threats (SWOT) analysis on OMF and summarizes how OMF applications can play a role to improve food security. This is further linked with short, medium and long terms policy interventions that can be deployed to achieve a more sustainable approach by balancing between protecting the wider environment and meeting food security.